Batteries: A Flexible 3D Multifunctional MgO‐Decorated Carbon Foam@CNTs Hybrid as Self‐Supported Cathode for High‐Performance Lithium‐Sulfur Batteries (Adv. Funct. Mater. 37/2017). (4th October 2017) - Xiang, Mingwu; Wu, Hao; Liu, Heng; Huang, Ju; Zheng, Yifeng; Yang, Li; Jing, Peng; Zhang, Yun; Dou, Shixue; Liu, Huakun
Abstract : In article number1702573, Heng Liu, Shixue Dou, and co‐workers report a design strategy for engineering a novel 3D, flexible, multifunctional hybrid composed of in‐situ N‐doped carbon foam@carbon nanotubes synchronously decorated with ultrafine magnesium oxide nanoparticles (CF@CNTs/MgO). This hybrid is directly used as an advanced self‐supported current collector to enhance the sulfur areal loading and mitigate the shuttling effect in high‐performance Li–S batteries.